Fetal origins of child non-right-handedness and mental health. - Rodriguez, Alina; Waldenström, Ulla (Journal of Child Psychology & Psychiatry & Allied Disciplines., 2008)
Background: Environmental risk during fetal development for non-right-handedness, an index of brain asymmetry, and its relevance for child mental health is not fully understood. Methods: A Swedish population-based prospective pregnancy-offspring cohort was followed-up when children were five years old (N = 1714). Prenatal environmental risk exposures were the number of ultrasound examinations and maternal distress during pregnancy. Child mental health, including symptoms of attention deficit hyperactivity disorder (ADHD), language difficulties, and care-seeking for child behavior problems, was assessed via maternal and/or kindergarten teacher's ratings. Results: Prenatal exposure to maternal depressive symptoms and critical life events were associated with increased risk of child non-right-handedness and mixed handedness, after adjustment for parity, maternal age, birth outcomes, infant sex, and parental handedness. No association was found between handedness and number of ultrasound examinations. Non-right and mixed-handedness, rather than left-handedness, were associated with increased risk of language difficulties and particularly with ADHD symptoms, after adjustment for current parental ADHD symptoms, current maternal depressive symptoms, birth outcomes, smoking during pregnancy, depressive symptoms and critical life events. Problems were significant enough to prompt mothers to seek care for children's behavioral problems, and parents were more likely to have received advice from the children's kindergarten teachers to seek care. Conclusions: This study suggests that mixed-handedness, i.e., reflecting atypical brain laterality, can be a marker of both severity of prenatal exposure to maternal distress and of increased risk of ADHD symptoms in childhood. Our results support the idea that the fetal environment plays a role in subsequent child mental health. Reprinted by permission of the publisher.